Progression Measurement of Visual Field Loss in Medically Controlled Primary Open-Angle Glaucoma (POAG): Visual field loss in POAG - Zehra, Maham; Anwar, Mohd Shakaib; Yousafzai, Erum; Akhter, Waseem; Ain, Qura -Tul-; Shafique, Maeirah (Pakistan Armed Forces Medical Journal, 2023)
Objective: To determine mean visual field parameters loss (Mean deviation and Pattern standard deviation) and frequency of glaucoma hemifield test to evaluate optic nerve damage progression in medically well-controlled primary open-angle glaucoma POAG through standard automated perimetry.Study Design: Prospective longitudinal study.Place and Duration of Study: Department of Ophthalmology, Rawal Institute of Health Sciences, Islamabad Pajistan, from Sep 2019 to March 2020.Methodology: Fifty-four patients were inlcuded. Visual field parameters included the Glaucoma hemifield test, Mean deviation, and Pattern standard deviation. The visual field loss progression was evaluated through Humphry analyzer 30-2. Follow-up was done on the first day of the presentation, then after three and six months.Results: We found an increase in intraocular pressure (14.59±1.3 vs 15.87±2.1, p